Effect of Corn Husk Powder Mixture on Mechanical Properties Using a Matrix Polyester and Vinylester - Ahyuda Ahyuda; Rahmat Fajrul (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of composite material technology continues to grow across various industries due to its advantages, including low density, high mechanical strength, and corrosion resistance. The use of synthetic fibers in composites has drawbacks in terms of environmental impact and production cost, making natural reinforcing materials such as corn husk powder a sustainable alternative. This study aims to determine the effect of adding corn husk powder on the mechanical and physical properties of a composite using a mixed matrix of polyester resin (70%) and vinylester resin (30%). The composites were fabricated using the hand lay-up method with corn husk powder mass variations of 0, 2, 5, 7, and 12 grams, and were tested for impact toughness using the Charpy method according to the ASTM D6110 standard. The results show that the addition of corn husk powder significantly increased the composite's impact toughness. Impact values increased progressively from 0.007 J/mm² at 0 grams, to 0.043 J/mm² (2 grams), 0.062 J/mm² (5 grams), 0.085 J/mm² (7 grams), reaching the highest value of 0.149 J/mm² at 12 grams. The 12-gram variation was identified as the best composition in this study, producing the highest absorbed energy and impact toughness. These results indicate that corn husk powder has strong potential as a natural reinforcing material in polyester–vinylester based composites, while also adding value to agricultural waste and supporting the development of environmentally friendly materials.